Digital health literacy is linked to attitudes regarding the ethical aspects of digital health among patients with dermatologic comorbidities - Ana Lilia Ruelas-Villavicencio; Irazú Contreras-Yáñez; Roxana Paola Gómez-Ruiz; María Clara Zagaglia Del Valle; Andrea Malagón-Liceaga; Virginia Pascual-Ramos (PLoS ONE, 2025)
Introduction Digital health literacy (DHL), also known as eHealth literacy, refers to an individual’s ability to locate, understand, evaluate, and apply health information from electronic sources to make informed health decisions. This skill is increasingly regarded as essential for navigating the modern healthcare landscape, promoting health equity, and improving health outcomes. The study objective was to establish an association between DHL and dermatologic outpatients’ attitudes regarding ethical aspects of digital health. Additionally, we validated a questionnaire designed to assess these bioethical attitudes. Patients and methods This cross-sectional study was performed in two phases (April 2024-December 2024). Phase-1 consisted of validating the Bioethical Attitudes toward Digital Health questionnaire (BADH). Phase-2 evaluated the association between the eHEALS (it assesses a person’s ability to use digital health resources) and BADH scores. Three convenience samples of consecutive patients were used: S-1 included 46 patients who participated in a pilot testing, S-2 included 100 patients who participated in the BADH validation and S-3 included 120 patients and was used to investigate the association between DHL and bioethical attitudes. Descriptive statistics and multiple linear regression analysis were used. Results The 8-item BADH was found to be feasible, valid, and reliable. The exploratory factor analysis revealed a two-factor structure, consisting of trust and privacy dimensions, which accounted for 59.8% of the total variance. This structure was subsequently validated through confirmatory factor analysis. The BADH reliability was confirmed with a Cronbach’s alpha of 0.686 and ICC of 0.684 (95% CI: 0.581–0.770). A positive linear association was identified between the eHEALS and the BADH scores (β = 0.465, 95%CI: 0.218–0.450, p < 0.001). This relationship was evident with the trust dimension of the BADH (β = 0.526, 95%CI: 0.206–0.379, p < 0.001), but not with the privacy dimension. Conclusions DHL is associated with individual moral positions regarding digital health, particularly those concerning trust. The BADH questionnaire has adequate psychometric properties.